Antecedents of Grievance Filing Behavior: Attitude/Behavioral Consistency and the Union Steward - Dalton, Dan R.; Todor, William D. (Academy of Management Journal, 1982)
In this study the grievance behavior of stewards, unlike rank and file members, was found to vary systematically with company commitment, union commitment, and job satisfaction. In addition, the relative lack of truncation imposed on the grievance behaviors of union stewards was found to result in attitudinal/behavioral consistency with respect to grievance filing behaviors.